Screening, Identification, and Application of Superior Starter Cultures for Fermented Sausage Production from Traditional Meat Products - Zijie Dong; Longfei Wang; Yanzheng Ge; Yongqiang An; Xiaoxue Sun; Ke Xue; Haoyang Xie; Ran Wang; Junguang Li; Lishui Chen (Fermentation, 2025)
In this study, 43 strains of Staphylococcus spp. and 22 strains of lactic acid bacteria (LAB), isolated from six representative fermented meat products (domestic and international), were subjected to a comprehensive safety evaluation, including hemolytic activity, catalase test, hydrogen sulfide production, and antibiotic susceptibility screening. Nine strains were selected for secondary screening based on safety criteria, fermentation characteristics, and acid and salt tolerance tests. Two optimal strains were identified—Staphylococcus saprophyticus LH-5 and Latilactobacillus sakei OFN-11—demonstrating excellent compatibility and no mutual antagonism. Both strains were non hemolytic, catalase positive, susceptible to some of the antibiotic tested, and did not produce hydrogen sulfide, mucus, or gas. These favorable fermentation characteristics included lipase/protease production, amino acid decarboxylase negativity, and salt and acid tolerance. Application experiments in fermented sausages were analyzed for 55 volatile compounds, related to meaty, fruity, and fatty aroma profiles compared to commercial starter cultures. The formulation including the selected strains exhibited lower acidity than its commercial unterparts while maintaining superior sensory and physicochemical attributes. These findings suggest that the S. saprophyticus LH-5 and L. sakei OFN-11 consortium holds promising potential as a starter culture for fermented meat products, offering technological advantages to become a fermentation agent that meets the preferences of Chinese consumers.